Coverage of National Spirit and Expression in the Translations of Uzbek Stories and Narratives - Abdukhafizovna, Khalimova Nilufar (Indonesian Journal Publisher, 2024)
This article explores the problems of reflecting the national spirit and specific modes of expression in the process of translation using the example of the English translation of the famous work of the Uzbek writer Gafur Ghulam “The Naughty Boy”. During the study, a comparative analysis of the text of the original work and its translation is carried out, assessing such aspects as the main criteria that determine the quality of translation - the preservation of the plot and composition, the issuance of national realities and phraseological units, the author’s style and the degree of reflection of the individuality of character speech. According to the results of the analysis, although the general content and artistic features of the work have been successfully restored in the translation of “The Naughty Boy”, problems are visible in the translation of certain national features, including realities, folk proverbs and phrases characteristic of the Uzbek lifestyle and mentality.